Seasonal to Decadal Western Boundary Current Variability From Sustained Ocean Observations - M. Chandler; N. V. Zilberman; J. Sprintall (Geophysical Research Letters)
Abstract Subtropical western boundary currents (WBCs) exert a substantial influence on regional climate. To improve WBC observations on seasonal‐to‐decadal timescales, and characterize their subsurface structure to 1975 m depth, we combine high‐resolution expendable bathythermograph, Argo, and satellite altimetry observations in the Agulhas Current, East Australian Current, and Kuroshio. The resulting 16 year time series (2004–2019) show a weakening trend in Kuroshio transport, but no trend in Agulhas transport or East Australian Current transport. All three WBCs have stronger transport in summer, driven mostly by changes in current speed rather than current width. This unique subsurface view of WBC variability reveals changes in the path of the Kuroshio Extension on interannual timescales, and eddy variability in the Agulhas. Our work highlights how this application of a consistent methodology to combine complementary ocean observations allows for an unprecedented direct comparison of variability between WBCs.